2009
DOI: 10.1161/circulationaha.108.797407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aortic and Cardiac Dysfunction in Uremic Mice With Aortic Calcification

Abstract: Background-Chronic renal failure (CRF) is associated with cardiac dysfunction and increased aortic stiffness. The mechanisms involved are not clearly understood. We examined changes over time in cardiac and aortic function in a murine CRF model. Methods and Results-Eight-week-old mice were randomly assigned to 1 of 4 groups: wild-type non-CRF, wild-type CRF, apolipoprotein E knockout non-CRF, and apolipoprotein E knockout CRF. Echocardiography was performed and blood samples were taken at baseline and after 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
45
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 31 publications
6
45
1
1
Order By: Relevance
“…We hypothesized that endothelium-dependent relaxation would be impaired in cerebral arterioles, as previously observed in the aorta (24).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…We hypothesized that endothelium-dependent relaxation would be impaired in cerebral arterioles, as previously observed in the aorta (24).…”
mentioning
confidence: 87%
“…The rationale for using female mice and two different strains is based on the observation that male and female WT mice do not develop calcification during CRF. In contrast, ApoE Ϫ/Ϫ mice develop arterial calcification during CRF (24), but the process is much slower in males than in females. Since vascular calcification may affect vascular structure and function, we wondered whether this would be true for the cerebral circulation.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The positive phosphate balance seems to cause an accelerated progression of vascular calcification. [5][6][7][8] An acute phosphate load that overwhelms renal capacity for excretion can be derived from endogenous and exogenous sources. Large amounts of endogenous phosphates are released from intracellular stores in tumor lysis syndrome, rhabdomyolysis, and lactic acidosis.…”
mentioning
confidence: 99%
“…We found that 769 genes were differentially expressed by the peak of hyperglycaemia, including a very important group implicated in arterial calcification and premature atherosclerosis [34][35][36][37]. Other genes included those involved in cell cycle, cell adhesion, antioxidant processes, inflammation and angiogenesis, and those encoding molecules involved in endothelial and smooth muscle cell function.…”
Section: Discussionmentioning
confidence: 98%